Pengaruh Pakan Pelet Complete Feed Berbasis Indigofera terhadap Hematologi Domba Garut Lepas Sapih: Effects of Indigofera-Based Pellet Complete Feed on The Hematological of Post-Weaning Garut Sheep - Sidiq, Fajar; L Abdullah; Didid Diapari (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
This study examined the effect of pellet diets containing varying levels of Indigofera on the hematological profile of post-weaning male Garut sheep. The study involved fifteen sheep (3-5 months old; body weight approximately 16.54±2.23 kg). The animals were divided into three dietary treatment groups differing in Indigofera and crude fiber content. The parameters observed in this study included the blood profile (erythrocytes, leukocytes, hemoglobin, and hematocrit) of the sheep before and after feeding the Indigofera-based complete feed pellets. The data obtained were analyzed using ANOVA in the form of a completely randomized design (RAK) with 3 treatments (P1 = 20% Indigofera with SK of 19%, P2 = 20% Indigofera with SK of 18%, P3 = 10% Indigofera with SK of 17% and 5 replication groups. Statistical analysis of the T-test was used to compare the data of blood profile values ​​before and after feeding. The results showed that the difference in Indigofera levels of 10-20% and crude fiber from 17-19% did not produce significant differences in hematological values ​​(erythrocytes, leukocytes, hemoglobin, and hematocrit) produced between treatments. Feeding Indigofera-based complete feed pellets provided physiological results that were still quite good.  It can be concluded that sheep hematology, namely the values ​​of erythrocytes, hemoglobin, and hematocrit produced, were in the normal range.